Update and harmonisation of guidance for the management of diabetic ketoacidosis in children and young people in the UK - Daniel B Hawcutt; Mark Deakin; Charlotte EM Rugg-Gunn (BMJ Publishing Group, 2021)
Diabetic ketoacidosis (DKA) is a life-threatening complication of type 1 diabetes mellitus. Careful and timely intervention is required to optimise glycaemic control and reduce the risk of mortality and devastating complications. Of these, cerebral oedema is the leading cause of death, with a mortality rate of approximately 25%. This article highlights the recent updates to UK fluid therapy guidelines for DKA and provides clinical context for the benefit of paediatricians and junior doctors in light of this new guidance.